2021
DOI: 10.5946/ce.2020.212
|View full text |Cite
|
Sign up to set email alerts
|

Superior Specimen and Diagnostic Accuracy with Endoscopic Ultrasound-Guided Liver Biopsies Using 19-Gauge versus 22-Gauge Core Needles

Abstract: Background/Aims: Endoscopic ultrasound-guided liver biopsy (EUS-LB) is an effective and safe method of procuring liver tissue. The aims of this study were to assess and compare the outcomes and tissue adequacy of a single-pass, single-actuation, wet suction technique between 19 G and 22 G needles in patients undergoing EUS-LB.Methods: We performed a prospective case series study of 20 patients undergoing EUS-LB at a single center between September 2017 and April 2020. The primary objective was to evaluate diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…When a comparison is made between EUS-LB with the standard of care percutaneous liver biopsy, a previous study by Bhogal et al found no difference between specimens from liver biopsy obtained by either method as regards the length of the longest piece and the number of portal tracts, although the tissue length was longer in percutaneous liver biopsy 27 . Similar studies have found similar diagnostic accuracy between EUS-LB (88.8 %) and percutaneous liver biopsy sample (100 %) ( P = 0.82) 28 . Therefore, it has been found that EUS-LB specimens are at least comparable to percutaneous liver biopsy specimens with a benefit to sample widely separated liver segments 14 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…When a comparison is made between EUS-LB with the standard of care percutaneous liver biopsy, a previous study by Bhogal et al found no difference between specimens from liver biopsy obtained by either method as regards the length of the longest piece and the number of portal tracts, although the tissue length was longer in percutaneous liver biopsy 27 . Similar studies have found similar diagnostic accuracy between EUS-LB (88.8 %) and percutaneous liver biopsy sample (100 %) ( P = 0.82) 28 . Therefore, it has been found that EUS-LB specimens are at least comparable to percutaneous liver biopsy specimens with a benefit to sample widely separated liver segments 14 .…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies with 19Gz needle for EUS guided liver biopsy has shown longer core length ( 2.5 cms vs 1.2 cms, p <0.00001) with more portal tracts (8.8 vs. 3, p<0.0001), and longer, intact, fragment length (0.75 cm vs. 0.32 cm, p<0.0006). [28] The major strength of the study was that the pathologists were blinded about the tissue sample and three separate pathologists were independently involved in the diagnosis. In addition, the EUS-LB was done by 3 operators that avoided bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers posit that the 22 G samples had greater fragmentation, leading to reduced intact specimen length and CPT, reducing histological adequacy. The advantage of 19 G compared to 22 G needle was also shown in core needles, where 19 G core needles had a greater CPT (8.8 vs 3, P < 0.0001), longer core length (2.5 cm vs 1.1 cm, P < 0.0001), and a higher rate of pathological diagnostic samples (85% vs 10%, P < 0.0001) when compared to 22 G core needles[ 35 ].…”
Section: Technique Of Eus-guided Liver Biopsymentioning
confidence: 96%
“…[ 7 8 9 ] Regarding the size of needle, emerging evidence suggests that 19 G needles are better than 22 G needles as several studies have reported higher tissue fragmentation and lesser adequate specimen with latter. [ 10 11 12 13 14 ] Recent randomized clinical trial (RCT) ( n = 40) comparing the tissue yields and adequacy of a 19 G FNA versus 19 G Franseen-tip core biopsy FNB needle for EUS-LB demonstrated longer LB specimen and more CPT with EUS FNB needle without any serious adverse events. [ 15 ]…”
Section: Eus-guided Liver Biopsymentioning
confidence: 99%